Determining financial uncertainty through the dynamics of Sukuk bonds and prices in emerging market indices - Muhammad Safdar Sial; Jacob Cherian; Abdelrhman Ahmad Meero; Asma Salman; Abdul Aziz Abdul Rahman; Sarminah Samad; Constantin Viorel Negrut (Risks, 2022)
The main focus of the study is to determine the financial uncertainty while examining the Sukuk bonds prices, Sukuk bond and global emerging market indices returns dynamics. The study, with a time period ranging from 2017 to 2020, applies the quantile regression technique. The study findings show that evidence of co-moment exists between the global emerging market index and Sukuk bond price returns, except the one. There is no impact of the financial uncertainty indicator reflected by the global volatility index (VIX) on the Sukuk index returns, and even this impact is negative for (VXEEM). The causal impact among the global emerging and Sukuk bond markets will help formulate future trading strategies in particular to Islamic bond markets.
Keywords: 330; financial uncertainty; quantile regression; Sukuk; VIX; VXEEM